Pediatric Tonsillar Synovial Sarcoma- Very Rare Localization: A Case Report and Review of the Literature - Koray YALÇIN; Gülen TÜYSÜZ; Mine GENÇ; İrem Hicran ÖZBUDAK; Alper Tunga DERİN; Kamil KARAALİ; Alphan KÜPESİZ; Elif GÜLER (Federation of Turkish Pathology Societies, 2020)
Tonsillar synovial sarcoma is an extremely rare entity and only 9 adult patients have been reported up to now. Here, we describe the first pediatric tonsillar synovial sarcoma of the literature in a patient who presented with a 2-month history of dysphagia and snoring. Clinical and radiological examinations showed that the tumor arose from the right palatine tonsil and narrowed the parapharyngeal space. An incisional biopsy from the palatine tonsil revealed the diagnosis of synovial sarcoma. The patient has underwent total tonsillectomy and received radiotherapy and chemotherapy because of the positive surgical margins. The patient is clinically in good condition and free of tumor 30 months after the initial diagnosis. We achieved a long-term complete remission with a combination of surgery, radiotherapy and chemotherapy in our case. Tonsillar synovial sarcoma should be kept in mind while dealing with tonsillar masses. We can conclude that a multidisciplinary approach is warranted while treating synovial sarcoma with this localization.